Antimicrobial susceptibility patterns and molecular characteristics of group B Streptococcus isolated from three major hospitals in Malaysia - Suhaimi, Mohd. Emir Shafiq (2015)
Group B Streptococcus (GBS) or also known as Streptococcus agalactiae can cause sepsis and meningitis in neonates and it also can promote serious mortality in immunocompromised patients and morbidity in pregnant women and non-pregnant adults. The Centers for Disease Control and Prevention (CDC) published guidelines for intrapartum antibiotic prophylaxis since 1996 and recommended penicillin or ampicillin as the drugs of choice for prevention of GBS disease. The objective of this study is to analyze distribution of serotypes and antimicrobial susceptibility patterns of sixty GBS isolates and their potential genetic relation by Random Amplified of Polymorphic DNA (RAPD) analysis so that it acts as an additional reference for intrapartum chemoprophylaxis against GBS infection. All GBS isolates were obtained from different patients admitting to Hospital Serdang, Universiti Kebangsaan Malaysia Medical Centre (UKMMC)and Hospital Kuala Lumpur from December 2012 until March 2014. Ten isolates from each invasive and colonizing site were collected from each hospital. Disc diffusion test used as pre-screening for detection of antimicrobial susceptibility of GBS isolates. D test was applied to check any inducible resistant for clindamycin after being induced by erythromycin and E-test was used to detect minimal inhibitory concentration (MIC) for GBS isolates resistant or intermediate to erythromycin, clindamycin and penicillin. Serotyping was performed by latex agglutination method using specific antisera against type Ia, Ib, II until IX antigens. The process was confirmed further by molecular approach using multiplex PCR. The genetic relation between the isolates was examined by RAPD typing using P2 and GBS2 primer. Composite dendrogram was constructed using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) method. Ninety-eight percent of the isolates (n = 59) were susceptible with penicillin (one isolate was recorded intermediate sensitive to penicillin) whereas 78 % (n = 47) and 88 % (n = 53) where susceptible to erythromycin and clindamycin. Serotype Ia was most common serotype, (n = 27, 45 %) followed by serotype III (n =10, 16.7%), V (n = 9, 15%), VI (n = 8, 13.3%), II (n =3; 5 %) VIII and VII (n = 2, n = 1; 3.3%, 1.7%). None for serotype Ib, IV and IX. Based on RAPD, the study showed a diverse genetic pedigree of all isolates in four major clusters. At 31 % of similarity, isolates were segregated in the dendrogram according to their isolation sites and location of hospitals. There were no obvious genetic linkages in relation to antimicrobial patterns and serotypes.This study preliminary suggest the occurrence of distinct GBS isolates in RAPD dendrogram and most of the GBS isolates that resistant toward erythromycin and clindamycin come from serotype III although serotype Ia being the most common detected in GBS isolates regardless of the isolation site and location.